2016
DOI: 10.3847/0004-637x/818/2/143
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Accurate Extinction Measurements for X-Ray Spectral Models

Abstract: Interstellar extinction includes both absorption and scattering of photons from interstellar gas and dust grains, and it has the effect of altering a sourceʼs spectrum and its total observed intensity. However, while multiple absorption models exist, there are no useful scattering models in standard X-ray spectrum fitting tools, such as XSPEC. Nonetheless, X-ray halos, created by scattering from dust grains, are detected around even moderately absorbed sources, and the impact on an observed source spectrum can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 31 publications
2
45
0
1
Order By: Relevance
“…Scattering on dust grains along the line of sight can have a significant impact on the observed X-ray spectra (Predehl & Schmitt 1995;Smith et al 2016). The main effect of dust scattering is to create a halo around the source, by removing flux from the line of sight.…”
Section: Dust Scatteringmentioning
confidence: 99%
“…Scattering on dust grains along the line of sight can have a significant impact on the observed X-ray spectra (Predehl & Schmitt 1995;Smith et al 2016). The main effect of dust scattering is to create a halo around the source, by removing flux from the line of sight.…”
Section: Dust Scatteringmentioning
confidence: 99%
“…With the default parameter values, less than 5% of the dust-scattering halo is included in the source spectrum, affecting the spectrum overall by less than 1%. However, it has been shown that the diskshaped approximation vastly underestimates the true amount of the scattering halo recaptured within a typical source extraction radius; it is also heavily affected by the dust grain size and spatial distribution Smith et al 2016). Performing the full dust-scattering calculations is timeconsuming and provides many degenerate solutions.…”
Section: Fits To the Swift J1745407-290015 Spectrummentioning
confidence: 99%
“…Understanding the X-ray obscuration properties of the interstellar medium (ISM) is crucial for modeling accretion from compact objects and for learning about the material properties of dust Smith et al 2016). In GC studies, the ISM column obtained from fitting the X-ray continuum spectrum is often used to draw conclusions about where the compact object is in relation to SgrA * (e.g., Kennea et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our dscat code 15 for the differential scattering cross section is based on the public 16 xscat package released by Smith et al (2016) that presents xspec table models of integrated scattering cross sections; that paper contains a detailed description of the methodology used in calculating dustscattering cross sections.…”
Section: Dscat: An Xspec Model For Differential Dust-scattering Crossmentioning
confidence: 99%
“…Following Smith et al (2016), we implemented four families of dust distributions as functions of grain size a: Mathis et al (1977, MRN77 hereafter) distribution, which consists of a combination of silicate and graphite grains, each following a distribution with a single slope of . The default values correspond to the parameter choices of the original MRN77 model.…”
Section: Dscat: An Xspec Model For Differential Dust-scattering Crossmentioning
confidence: 99%